Multidimensional analyses of the learning curve for single‐incision plus one port laparoscopic surgery for sigmoid colon and upper rectal cancer. Issue 7 (17th April 2018) - Li, Junmeng; Wang, Yanan; Liu, Dong; Zhou, Haipeng; Mou, Tingyu; Li, Guoxin; Deng, Haijun
Abstract : Background and Objectives: Single‐incision plus one port surgery (SILS + 1) provides the advantages of being minimally invasive and easier to perform than pure single‐incision laparoscopic surgery. The aim of this study was to investigate the learning curve (LC) for SILS + 1 for sigmoid colon and upper rectal cancer. Method: From November 2012 to May 2014, a series of 85 consecutive patients underwent selective SLIS + 1 for sigmoid colon and upper rectal cancer performed by a single surgeon at Nanfang Hospital. The LC for SILS + 1 was evaluated using cumulative sum control chart (CUSUM) and risk‐adjusted CUSUM methods. Data for all the perioperative variables and pathologic results among the phases were compared. Results: The LC had three phases: phase 1 (cases 1‐13) was the initial learning period; phase 2 (cases 14‐44) was the learning plateau period; and phase 3 (cases 45‐85) was the competent period. The differences in total operating time among the three phases were significant. The number of harvested lymph nodes increased along with increases in the surgeon's experience. Conclusions: For experienced CLS surgeons, the learning process reached the plateau period after the 13th case, and technical competence was achieved after the 44th case.